Comparison Of The Performance Of Sharia Stock Mutual Funds With The Performance Of Conventional Stock Mutual Funds - Arivetullatif, Arivetullatif; Sulastri, Sulastri (Al-Hijrah: Journal of Islamic Economics And Banking, 2023)
This study aims to determine the differences in the performance of Islamic stock mutual funds with the performance of conventional stock mutual funds. This type of research is a descriptive statistical analysis with a sample population of Islamic stock mutual funds and conventional stock mutual funds that are actively listed on the IDX for the 2016-2020 period. The sample selection used the purpose sumpling technique. Purpose sampling method is a sampling method based on certain criteria. The method used is the Independent Sample T Test different test. The mutual funds tested were the performance of sayriah stock mutual funds and the performance of conventional stock mutual funds based on the value of return and risk of mutual funds using the Sharpe, Treynor, Jensen and MM methods. The results of this study indicate that there is a significant difference between the performance of Islamic stock mutual funds and the performance of conventional stock mutual funds.